Adaptação transcultural do Pictorial Personality Traits Questionnaire for Children (PPTQ-C) para o português brasileiro - Pedro Saulo Rocha Martins (2021)
The five-factor model of personality (FFM) has been trending in its use in childhood. The study of the FFM with children should have good, valid, and reliable instruments. In this dissertation, we presented two studies focused on the FFM with children: (a) Instruments for child personality assessment using the Five-Factor Model: a systematic review, and (b) transcultural adaptation of the Pictorial Personality Traits Questionnaire for Children (PPTQ-C) for the Brazilian Portuguese. In the first study, we reviewed the instruments available to assess the FFM in middle and late childhood. The instruments were evaluated in some of its psychometric properties. In general, less instruments are available for children when compared to other age-groups. The results were discussed taking into account the characteristics of psychological assessment with children. In the second study, we presented the results of the transcultural adaptation of the PPTQ-C (PPTQ-C [BR] in its Brazilian version). The PPTQ-C is a Polish self-report questionnaire that is based on the FFM. The PPTQ-C was designed to be used with children in middle and late childhood (~ 7 to 13 years). The questionnaire uses pictures to facilitate the general understanding of its items. In this study, we focused on the PPTQ-C version made for children with less than 10 years. The final sample comprised 179 children aged between 5 and 10 years (mean age = 7.74 standard-deviation = 1.16), 51.40% boys. Children were assessed at school site (n = 106) and through the internet (n = 73), due to the new coronavirus pandemic. All children answered the PPTQ-C (BR) and only a subsample (n = 92) answered another personality questionnaire and a scale design to assess positive and negative affect. The results suggest initial evidence in favor of the FFM in both designs of assessment (PPP = 0,433 – overall sample; PPP = 0,477 – in person assessment; PPP = 0,525 web assessment). However, the overall factor structure showed low differentiation, and there were high cross-loadings. Factor reliabilities were generally low (α ranging between 0.46 – 0.67). Correlation analysis revealed low convergent validity between PPTQ-C (BR) scores and the other questionnaires. Furthermore, there was no differences between genders (boys compared to girls). The developmental trends in the PPTQ-C scores could reveal differences in children self-awareness. The results were discussed taking into account methodological differences between this study and the original PPTQ-C study. In general, results suggest that the PPTQ-C (BR) still needs more studies with a higher and more heterogenous samples.